Interfamily wide hybridization between daylily (Hemerocallis, Xanthorrhoeaceae) and lycoris (Lycoris, Amaryllidaceae). (17th October 2022) - Lv, Yi; Gao, Yike; Cui, Yuxuan; Wang, Ying; Fan, Zhuping; Guan, Chunjing; Zhang, Qixiang
Abstract: Daylily ( Hemerocallis ) is a perennial with high ornamental value. It is difficult to obtain innovative daylily germplasm by conventional crossbreeding. To enrich the genetic variation of Hemerocallis, daylily was used as male parent to cross with lycoris ( Lycoris ). Artificial pollination and embryo rescue were performed to overcome reproductive isolation. Cross‐compatibility and pollen germination were analysed to investigate interfamily reproductive isolation. Leaf morphological analysis and inter‐simple sequence repeat (ISSR) were performed to identify the hybrid at seedling stage. Results showed that most pollen grains failed to adhere to stigmas, and pollen tubes germinated in a disordered direction. Ten days after pollination, 77.19% of ovaries aborted. Ovaries were harvested only in 10 hybridization combinations, the fruit setting rates were 7.69%–42.86%, and the ovule numbers were 0–6.0 per ovary. One embryo developed into plantlets eventually, whose parental combination was L. aurea  ×  H . 'My Complementary'. The hybrid was identified and exhibited both intermediate and novel characteristics of parents. This research is the first attempt to explore a protocol to obtain interfamily hybrid between daylily and lycoris.